Organizational culture and the credit portfolio recovery process - Puente Riofrío, Mariana Isabel; Dávalos Mayorga, Eduardo Ramiro; Ordoñez Sagnaí , Carla Lisbeth; Uquillas Granizo, Gilma Gabriela (mktDESCUBRE, 2023)
This research analyzes the relationship between organizational culture and the loan portfolio recovery process of an Ecuadorian credit institution, a non-experimental design was used, whose type of research is descriptive, structured surveys were used in the “Cooperativa de Ahorro y Crédito Crecer Ltda”. to evaluate the study variables. In the data analysis, non-parametric tests such as Wilcoxon and Friedman were applied to determine the differences between the variables, it is established that the recovery of the loan portfolio is not only linked to the organizational culture within an entity, but external factors that determine the state of the environment in which the entity and the clients relate to each other should also be considered. It was concluded that organizational culture is a critical factor that must be considered in the design and implementation of effective credit recovery processes in financial companies. The recovery of the loan portfolio should be understood under a criterion in which if there is no favourable environment, the productivity of entity, and the capacity of clients to meet its obligations will be reduced.